Traumatic and Spontaneous Vertebral Artery Dissections: An Analysis of Tertiary-Center 310 Patient Cohort. Issue 5 (14th August 2021) - Prasad, Nikil; Mitra, Akash; Shlobin, Nathan A; Azad, Hooman A; Cloney, Michael B; Hopkins, Benjamin S; Jahromi, Babak S; Potts, Matthew B; Dahdaleh, Nader S
Abstract: BACKGROUND: Vertebral artery dissections (VADs) are rare yet potentially devastating events. While the etiology of these events is either traumatic or spontaneous, there is a paucity of quantitative literature comparing the two. OBJECTIVE: To identify differences in predisposing factors, event characteristics, and clinical outcomes between traumatic VADs (tVADs) and spontaneous VADs (sVADs). METHODS: We retrospectively identified patients with VADs presenting to our institution at VAD onset with at least a 3-mo follow-up. Demographics, event characteristics, treatment details, and neurological outcomes as modified Rankin scale (mRS) scores were collected. RESULTS: Of the 310 patients sustaining 366 VADs total, 187 (60.3%) patients experienced a total of 221 (60.4%) sVADs and 123 (39.7%) patients experienced a total of 145 (39.6%) tVADs. sVADs were more likely to occur in the intracranial course of the artery ( P = .042) and have a lower mRS at discharge, 3-month, and last clinical follow-up ( P = 003, .002, and .001, respectively). tVADs were more likely associated with concomitant fractures ( P < .001). CONCLUSION: Despite similar patient populations, tVADs are associated with higher mRS scores at all time points. Although further study is needed, this may suggest other concomitant trauma rather than the VAD itself is contributing to worse neurological status in patients with tVADs. Graphical Abstract: